Local- and regional-scale air pollution modelling (PM10) and exposure assessment for pregnancy trimesters, infancy, and childhood to age 15 years: Avon Longitudinal Study of Parents And Children (ALSPAC). (April 2018) - Gulliver, John; Elliott, Paul; Henderson, John; Hansell, Anna L.; Vienneau, Danielle; Cai, Yutong; McCrea, Adrienne; Garwood, Kevin; Boyd, Andy; Neal, Lucy; Agnew, Paul; Fecht, Daniela; et al.
Abstract: We established air pollution modelling to study particle (PM10 ) exposures during pregnancy and infancy (1990–1993) through childhood and adolescence up to age 15 years (1991–2008) for the Avon Longitudinal Study of Parents And Children (ALSPAC) birth cohort. For pregnancy trimesters and infancy (birth to 6 months; 7 to 12 months) we used local (ADMS-Urban) and regional/long-range (NAME-III) air pollution models, with a model constant for local, non-anthropogenic sources. For longer exposure periods (annually and the average of birth to age 8 and to age 15 years to coincide with relevant follow-up clinics) we assessed spatial contrasts in local sources of PM10 with a yearly-varying concentration for all background sources. We modelled PM10 (μg/m 3 ) for 36, 986 address locations over 19 years and then accounted for changes in address in calculating exposures for different periods: trimesters/infancy (n = 11, 929); each year of life to age 15 (n = 10, 383). Intra-subject exposure contrasts were largest between pregnancy trimesters (5 th to 95 th centile: 24.4–37.3 μg/m 3 ) and mostly related to temporal variability in regional/long-range PM10 . PM10 exposures fell on average by 11.6 μg/m 3 from first year of life (mean concentration = 31.2 μg/m 3 ) to age 15 (mean = 19.6 μg/m 3 ), and 5.4 μg/m 3 between follow-up clinics (age 8 to age 15). Spatial contrasts in 8-year average PM10 exposures (5 th to 95 th centile) were relatively low: 25.4–30.0 μg/m 3 to age 8 years and 20.7–23.9 μg/m 3 from age 8 to age 15 years. The contribution of local sources to total PM10 was 18.5%–19.5% during pregnancy and infancy, and 14.4%–17.0% for periods leading up to follow-up clinics. Main roads within the study area contributed on average 3.0% to total PM10 exposures in all periods; 9.5% of address locations were within 50 m of a main road. Exposure estimates will be used in a number of planned epidemiological studies. Graphical abstract: Unlabelled Image Highlights: PM10 exposure assessment for a large birth cohort (pregnancy, infancy, childhood) Separate exposures for local (main roads, other) and regional/long-range sources. Primary PM10 from local major roads on average was 3% of total PM10 exposures. Largest contrasts for pregnancy trimesters (5 th to 95 th centile: 24.4–37.3 μg/m 3 ) Mean PM10 exposures fell from 31.2 μg/m 3 age 1 to 19.6 μg/m 3 age 15 years.